Effect of preconditioning on silver leaching and bromide removal properties of silver-impregnated activated carbon (SIAC) - Rajaeian, B.; Allard, Sebastien; Joll, Cynthia; Heitz, Anna (IWA Publishing, 2018)
Silver impregnated activated carbon (SIAC) has been found to be effective in mitigating the formation of brominated-disinfection by products during drinking water treatment. However, there are still uncertainties regarding its silver leaching properties, and strategies for the prevention of silver leaching have remained elusive. This study focused on the evaluation of one type of commercially available SIAC for its ability to remove bromide while minimising silver leaching from the material. Both synthetic and real water matrices were tested. Depending on solution pH, it was found that changing the surface charge properties of SIAC, as measured by the point of zero charge pH, can result in additional bromide removal while minimising the extent of silver leaching. To better understand the mechanism of silver leaching from the SIAC, eight preconditioning environments, i.e. variable pH and ionic strength were tested for a fixed amount of SIAC and two preconditioning environments were selected for a more detailed investigation. Experiments carried out in synthetic water showed that preconditioning at pH 10.4 did not deteriorate the capacity of SIAC to remove bromide, but significantly decreased the release of silver in the form of ionic silver (Ag + ), silver bromide (AgBr) and silver chloride (AgCl) from 40% for the pristine to 3% for the treated SIAC. This was confirmed using a groundwater sample. These results suggest that preconditioned SIAC has the potential to be an effective method for bromide removal with minimised silver leaching in a long-term field application for drinking water production.